Pelatihan Pembuatan Produk Sepatu Menggunakan Teknik Copy of Last di DIT Mwanza Tanzania - Abimanyu Yogadita Restu Aji; Rofiatun Nafiah; Mochammad Charis Hidayatullah (JPM: Jurnal Pengabdian Masyarakat, 2025)
Vocational education and training are one of the main priorities in improving the quality of human resources in various countries. This training program aims to improve capacity and competence in developing countries through sharing knowledge and experience. One of its main initiatives is the Expert Dispatch Program, which sends instructors from ATK Polytechnic to provide technical assistance related to shoe making at DIT (Dar es Salaam Institute of Technology) Mwanza, Tanzania. The implementation of this activity is divided into 3 stages: 1) Preparation, 2) Implementation, 3) Evaluation of activities. Shoe making begins with manual design making, followed by pattern making using measurable methods, cutting materials and the shoe making process. The results of the series of shoe making processes from design activities to shoe making can be said to be going well, this is evidenced by the results of the training participants' shoes meeting the assessment aspects including neatness, suitability and visual appearance. The level of understanding of the participants regarding the training material provided is categorized as good. A total of 25 participants with an indicator of 21 participants experiencing an increase in understanding the material that has been delivered is a good and positive thing, and provides a conclusion that there is a new value/understanding/knowledge that has been received, understood, and comprehended by participants during the 12 days of training. The instructor succeeded in delivering the material and meeting the needs of the participants, with an average total evaluation point reaching 4.77 (good). The assessment of all aspects of the activity including material and theme, instructor, training method, facilities and implementation showed an average value of 4.63 (good)